Repression of Enzymes of Arginine Biosynthesis by l-Canavanine in Arginyl-Transfer Ribonucleic Acid Synthetase Mutants of Escherichia coli - Faanes, Ronald (1972)
We show that the arginine analogue, l-canavanine, repressed the accumulation of translatable messenger ribonucleic acid (RNA) for three arginine biosynthetic enzymes in Escherichia coli. The method used to determine the level of translatable messenger RNA depended upon measurement of a burst of enzyme synthesis as described previously. E. coli strains with defective arginyltransfer ribonucleic acid (tRNA) synthetase (argS mutants) were insensitive to canavanine repression. When deprived of leucine, a leu argS strain regained normal sensitivity to canavanine repression. The level of in vivo canavanyl-tRNA(arg) was determined for a normal strain and an argS mutant. After 20 min of growth with canavanine only 9% of tRNA(arg) from the argS strain was protected from periodate oxidation, while 42% of the tRNA(arg) from an argS(+) strain was charged. When deprived of leucine, leu argS or leu argS(+) strains grown with canavanine contained more than 60% charged tRNA(arg). Reverse phase column chromatography of periodate-oxidized tRNA from canavanine-grown argS and argS(+) strains showed no preferential charging of any isoaccepting species of tRNA(arg). Therefore, we failed to detect a specific arginyl-tRNA species that might be involved in repression by canavanine. However, the data suggest that canavanine repression of the arginine pathway occurs only when high levels of canavanyl-tRNA are present, and thus support the notion that arginyl-tRNA synthetase plays a role in generating a repression signal.